Analysis of Village Resilience Based on the 2024 Village Development Index in Bunga Raya Subdistrict - Taryono, Taryono; Jovanka, Asri Dwi; Nofa, Tasya; Yasmin, Nazwa Azura; Khonsa, Hana Dallilah; Wadani, Nabila Cantika (Universitas Dharmawangsa Medan, 2025)
This research aims to analyse the level of village resilience based on the 2024 Village Development Index (IDM) in Bunga Raya Subdistrict, Siak Regency, Riau Province. The three main dimensions examined include the Social Resilience Index (IKS), Economic Resilience Index (IKE), and Environmental Resilience Index (IKL), which reflect the ability of villages to provide basic services, strengthen economic independence, and maintain environmental sustainability. This study presents the latest empirical analysis using 2024 IDM data to assess multidimensional village resilience at the subdistrict level, which has rarely been done before. The results of this study enrich the study of rural development by identifying the balance between social, economic, and environmental dimensions in achieving the status of an Independent Village. This study uses a descriptive quantitative approach with secondary data from the 2024 IDM published by the Ministry of Villages, Disadvantaged Regions, and Transmigration of the Republic of Indonesia. All villages in Bunga Raya Sub-district have achieved ‘Independent Village’ status with an IDM value above 0.8; the highest being Bunga Raya Village (0.9167). Village development in Bunga Raya Subdistrict shows good multidimensional balance, but continuous efforts are still needed to strengthen local economic institutions, improve social capacity, and preserve the environment.